Clinical significance of in-hospital reocclusion after mechanical reperfusion and percutaneous transluminal coronary angioplasty for acute myocardial infarction - Munhoz,Eva Cantalejo (2000)
OBJECTIVE: To analyze the effects of in-hospital reocclusion of reperfused AMI culprit coronary arteries in mortality and to identify the predictors. METHODS: The present study comprises a sample of 155 patients with AMI who underwent successful mechanical reperfusion by direct coronary angioplasty and angiographic control during hospitalization or before discharge. Patients were classified into group A: reoccluded patients (n=30) and group B: non-reoccluded patients (n=125). RESULTS: We identified in-hospital reocclusion predictors and found a greater significance in mortality among reoccluded patients (23,3% x 1.6%; p=0.00004). Silent reocclusion or typical angina at reocclusion had a good prognosis. The independent predictors of in-hospital mortality were hypertension, multiarterial lesions, totally occluded AMI culprit lesions, failed redilatation, failed redilatation in comparison with no intention to redilate, no redilatation in comparison with no atempt to redilate, and reocclusion within the first 48 to 72 hours. The decision to redilate, independently of the result, led to a 50.0% reduction in hospital mortality (p=0.0366). CONCLUSION: In-hospital AMI culprit coronary artery reocclusion had an adverse effect similar to that reported in clinical studies with high mortality rates (23.3% x 1.6%; p=0.00004). The major contribution of this study is to recommend the reopening of reoccluded AMI culprit coronary arteries as a means for the management of coronary artery reocclusion.